Projekty innowacyjne w przedsiębiorstwach jako potencjalne źródło ryzyka finansowego - Bacior, Michał (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2016)
Increase in the value of a company is related to implementation of innovative processes in all functional areas of business. As a result of implemented innovation, the company may offer new products or lower prices. In any case, this leads to improved economic efficiency of the company. The rise in innovation is coupled with an increase in the benefits but is also accompanied by an increase of the risk of failure. This constitutes background against which the article presents the course of innovation processes and possibilities of applying innovation in different market strategies. The article stresses relations between financial risk and the time of innovation. Sources of financial risk and methods of financing innovative investments are also discussed as is the need to take into account the technological environment and market context of innovation